2014
DOI: 10.17265/2161-6221/2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology Optimization of Dibenzothiophene Biodesulfurization in Model Oil by Nanomagnet Immobilized Rhodococcus Erythropolis R1

Abstract: Abstract:Rhodococcus erythropolis R1 is a capable strain in bioconversion of dibenzothiophene (DBT) to 2-hydroxybiphenyl (2-HBP) in oil model. In order to prevent the contamination of biodesulfurization (BDS) products by free cells, microbial cells were immobilized using different materials such as magnetic Fe 3 O 4 nanoparticles (NPs). In this study, magnetic NPs were produced by two different procedures and their characteristics were determined via transmission electron microscopy (TEM) and X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Chang et al [ 51 ] found that the high rate of degradation at optimal pH is linked to the transfer of dye molecules through the cell membrane, which is the rate-limiting stage in degradation. Changes in pH can influence not just the shape of an enzyme, but also the shape or charge characteristics of the substrate, which prevents the substrate from binding to the active site or undergoing catalysis, according to Etemadifar et al [ 52 ]. Rajeswari et al [ 53 ] discovered that the maximal removal of reactive dyes by employing Lysinibacillus sphaericus RSV-1 was 94.37% and 91.99% at pH 7 and 9, respectively, after 36 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al [ 51 ] found that the high rate of degradation at optimal pH is linked to the transfer of dye molecules through the cell membrane, which is the rate-limiting stage in degradation. Changes in pH can influence not just the shape of an enzyme, but also the shape or charge characteristics of the substrate, which prevents the substrate from binding to the active site or undergoing catalysis, according to Etemadifar et al [ 52 ]. Rajeswari et al [ 53 ] discovered that the maximal removal of reactive dyes by employing Lysinibacillus sphaericus RSV-1 was 94.37% and 91.99% at pH 7 and 9, respectively, after 36 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, magnetite nanoparticles were immobilized on the surface of Pseudomans delafieldii , Rhodococcus erythropolis LSSE8-1, and Rhodococcus erythropolis IGTS8 bacterial cells, where the desulfurization activity and reusability of magnetite coated bacteria were evaluated (19, 20, 22, 23). On the other hand, in our prior study, we coated R. erythropolis IGTS8 and R. erythropolis FMF with glycine-modified magnetite nanoparticles and investigated the effect of magnetite nanoparticles on the desulfurization activity of bacterial strains (24).…”
Section: Introductionmentioning
confidence: 99%